Capital Budgeting: Maledia Broadcasting Ltd. Issue 2 (September 2020) - Purani, Keyoor; Jeesha, Krishnan
In 2011, Samjad, deputy CEO of Maledia Broadcasting Limited (MBL)—a new venture of the media group Maledia, based in Cochin, India—prepared to make financial projections to justify the feasibility of the new Malayalam news channel. He was faced with challenges of making estimates that made the project attractive yet practical and credible for the group that was conservative in their advertising sales approach. Set in an interesting industry like broadcasting, the case simulates a real-life situation that also provides a internal corporate context. With the help of the rich market data such as advertising spends, commercial time, competitive scenario in the region, students are expected to forecast revenue for the project. Students are also challenged to use benchmark data of competitors to estimate hurdle rate, capex and operating costs. Estimation of initial investments is also required to be made. Using the processed financial data and projections, students are required to prepare discounted cash flows (DCF) statements with net present value (NPV) and internal rate of return (IRR) for the broadcast channel project. They learn to build alternate scenarios to deal with decisions under uncertainty. The case provides several opportunities to discuss narratives and numbers, helping students of finance realize the value of analysing the company policies and values, business situation, market environment and competitive financial information in capital budgeting, and project finance beyond number crunching.